Proyecto de factibilidad para la instalación de una empresa de confección de ropa casual infantil en el cantón Quevedo, provincia de Los Ríos. período 2012 - Véliz Macías, María Trinidad (2013)
The present study was framed within the modality of feasible project, oriented to the installation and commissioning of a clothing company of casual clothing child, located in the city of Quevedo, Los Ríos province. Among the objectives was raised: develop a market study that determine and quantify the supply, demand and marketing of products made by the company, carry out the technical study for the development of children's casual clothing, planning strategies and distribution that allows optimal and timely place products of children's clothing, also carry out economic and financial analysis to demonstrate the feasibility of the project. The design of the research, was descriptive, since it was developed with primary sources processed through the application of a survey questionnaire, the owners or managers of commercial establishments. The study was conducted on a sample of ten commercial establishments in the city. Among the results of the investigation determined that there is an unmet demand for 75,112 clothing. The investment required for the project turned out to be $51,671.92, which 70% will be covered by financing from a financial institution and the remaining 30% for own contribution. The amount of the annual costs of the activities of "Peke's" $68,268.31 has divided it is in fixed costs and variable costs $9,910.00 raised the price of all items that are nicely both children giving a total income of $88,990. Finalizing calculations and financial analysis determined the feasibility of the project, because that gets a point of equilibrium in the first year by $76,823.41; VAN $8,578.88; TIR 21% and relationship benefit cost of 1.25.